Argatroban Anticoagulation for Adult Extracorporeal Membrane Oxygenation: A Systematic Review. (April 2022) - Geli, Janos; Capoccia, Massimo; Maybauer, Dirk M.; Maybauer, Marc O.
Background: Heparin is the widely used anti-coagulation strategy for patients on extracorporeal membrane oxygenation (ECMO). Nevertheless, heparin-induced thrombocytopenia (HIT) and acquired anti-thrombin (AT) deficiency preclude the use of heparin requiring utilization of an alternative anticoagulant agent. Direct thrombin inhibitors are being proposed as potential alternatives with argatroban as one of the main agents. We aimed to review the evidence with regard to safety and efficacy of argatroban as a potential definitive alternative to heparin in the adult patient population undergoing ECMO support. Methods: A web-based systematic literature search was performed in Medline (PubMed) and Embase from inception until June 18, 2020. Results: The search identified 13 publications relevant to the target (4 cohort studies and 9 case series). Case reports and case series with less than 3 cases were not included in the qualitative synthesis. The aggregate number of argatroban treated patients on ECMO was n = 307. In the majority of studies argatroban was used as a continuous infusion without loading dose. Starting doses on ECMO varied between 0.05 and 2 μg/kg/min and were titrated to achieve the chosen therapeutic target range. The activated partial thormboplastin time (aPTT) was the anticoagulation parameter used for monitoring purposes in most studies, whereas some utilized the activated clotting time (ACT). Optimal therapeutic targets varied between 43-70 and 60-100 seconds for aPTT and between 150-210 and 180-230 seconds for ACT. Bleeding and thromboembolic complication rates were comparable to patients treated with unfractionated heparin (UFH). Conclusions: Argatroban infusion rates and anticoagulation target ranges showed substantial variations. The rational for divergent dosing and monitoring approaches are discussed in this paper. Argatroban appears to be a potential alternative to UFH in patients requiring ECMO. To definitively establish its safety, efficacy and ideal dosing strategy, larger prospective studies on well-defined patient populations are warranted.